Insecticide resistance in the Cydia pomonella (L): Global status, mechanisms, and research directions - Ju, Di; Mota-Sanchez, David; Fuentes-Contreras, Eduardo; Zhang, Ya-Lin; Wang, Xiao-Qi; Yang, Xue-Qing (Pesticide biochemistry and physiology, 2021)
The codling moth, Cydia pomonella (Lepidoptera: Tortricidae) is a major pest of pome fruit and walnuts worldwide. Although environmentally compatible integrated control strategies, such as mating disruption, attract-kill strategy, and sterile insect technique have been conducted for management of this notorious pest, effects to control of codling moth have mainly relied on insecticides. In consequence, different levels of insecticide resistance towards organophosphates, neonicotinoids, hydrazines, benzoylureas, pyrethroids, diamides, spinosyns, avermectins, JH mimics, carbamates, oxadiazines and C. pomonella granulovirus (CpGVs) have developed in codling moth in different countries and areas. Both metabolic and target-site mechanisms conferring resistance have been revealed in the codling moth. In this review, we summarize the current global status of insecticide resistance, the biochemical and molecular mechanisms involved, and the implications for resistance management. [Display omitted] •The coding moth (CM) has developed resistance to almost all classes of insecticides.•Target-site and metabolic mechanisms are involved in insecticide resistance in CM.•Resistance management strategy for preventing resistance development is proposed.•Genomic technologies open an avenue for developing management programs in CM.